2016
DOI: 10.1021/acsami.6b06083
|View full text |Cite|
|
Sign up to set email alerts
|

Simultaneously Tailoring Surface Energies and Thermal Stabilities of Cellulose Nanocrystals Using Ion Exchange: Effects on Polymer Composite Properties for Transportation, Infrastructure, and Renewable Energy Applications

Abstract: Cellulose nanocrystals (CNCs) have great potential as sustainable reinforcing materials for polymers, but there are a number of obstacles to commercialization that must first be overcome. High levels of water absorption, low thermal stabilities, poor miscibility with nonpolar polymers, and irreversible aggregation of the dried CNCs are among the greatest challenges to producing cellulose nanocrystal-polymer nanocomposites. A simple, scalable technique to modify sulfated cellulose nanocrystals (Na-CNCs) has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 68 publications
5
57
0
Order By: Relevance
“…These attractive properties, especially when coupled with chemical and/or physical modifications that influence function, provide a platform for the development of advanced materials based on cellulose. In fact, during the past several decades, studies have shown that surface modifications of cellulose produce functional surfaces that can be used for high‐value‐added applications in areas as diverse as composite materials, flexible organic electronics, biomedical applications, microfluidic devices, self‐cleaning surfaces, and oil–water separation systems …”
Section: Introductionmentioning
confidence: 99%
“…These attractive properties, especially when coupled with chemical and/or physical modifications that influence function, provide a platform for the development of advanced materials based on cellulose. In fact, during the past several decades, studies have shown that surface modifications of cellulose produce functional surfaces that can be used for high‐value‐added applications in areas as diverse as composite materials, flexible organic electronics, biomedical applications, microfluidic devices, self‐cleaning surfaces, and oil–water separation systems …”
Section: Introductionmentioning
confidence: 99%
“…Epoxide content (275 g/equiv) was determined by titration with 0.1 N HBr in acetic acid using a crystal violet endpoint. Cellulose nanocrystals were exchanged using the process described previously [41]. The epoxy composites were prepared by in the following manner.…”
Section: Methodsmentioning
confidence: 99%
“…A method has recently been developed to modify the surface of sulfated cellulose nanocrystals using a simply, scalable ion exchange process [41]. In this approach, rather than adding a surfactant, the sodium cation is exchanged with a surfactant cation.…”
Section: Ion Exchange Of Cellulose Nanocrystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…45 MD simulations have been successfully used to study CNC-based materials, which not only corroborate experimental ndings, 46,47 but have also revealed important structural and interfacial mechanisms that contribute to their superior mechanical performance, offering guidance for experimental material design. [48][49][50] Recently, we established an atomistically informed coarse-grained modeling approach to extend analyses of CNCs to larger length and time scales, which has been instrumental in explaining the inuence of overlap length and interfacial interactions on the mechanical properties of neat CNC nanopapers up to micrometer sizes. 51 With the advent of small-scale ballistic experiments, such as laser-induced projectile impact tests (LIPIT), 52,53 MD simulations have successfully been used to explain the failure mechanisms of nanomaterials subjected to ballistic impacts.…”
Section: Introductionmentioning
confidence: 99%